TRENDS REGARDING THE ROLE OF THE SETTER IN VOLLEYBALL - Alina RUSU (Cluj University Press, 2017)
During time, it has been found that the setter plays an important role in the team game. In what concerns the volleyball, the setter holds the most important position in the team, being the most valuable player, his/her opinions being highly respected by the teammates. Nowadays, the volleyball has significantly evolved by fast and unpredictable offenses, strong defensive, forceful serves with the highest speeds. The setter is also called as the team coordinator. Beside the remarkable physical qualities the setter has, he/she is a kind of team psychologist, notices the teammates reactions in difficult and crucial moments, anticipates some affective states in certain phases of the game, and therefore together with the trainer, the setter is able to manage the situation as best possible. REZUMAT. Tendințe ale rolului ridicătorului în jocul de volei. Pe parcursul anilor s-a demonstrat că în jocurile de echipă un rol important îl joacă ridicătorul acesteia. În jocul de volei acesta este cel mai important pion din teren al echipei, fiind cel mai bun și respectat de ceilalți coechipieri. Jocul de volei de astăzi a progresat foarte mult, prin atacuri rapid, neașteptate, apărare fermă, servicii în forță și cu viteză foarte mare. Ridicătorul, în jocul de volei a mai fost numit și coordonatorul echipei. Acesta pe lângă calitățile fizice deosebite pe care le are, el este și un fel de psiholog al echipei, observând reacțiile acesteia în unele momente dificile, de cumpănă, a coechipierilor, anticipează unele stări afective in anumite faze ale meciului, astfel putând împreună cu antrenorul să gestioneze cât mai bine situația. Cuvinte cheie: volei, calități, ridicător, coordonator.